Analisa Numerik Perilaku Aliran yang Melalui Struktur Persegi - La Ode Ahmad Barata; Lukas Kano Mangalla; Amrullah (Piston: Jurnal Teknologi, 2023)
This study is designed to analyze the flow characteristics aver a square body with variations in the angle of attack of the flow. The force components u, CD, -CPb, CL and St are analyzed numerically. The method used in this research is the Large Eddy Simulation (LES) turbulent model with variations in the angle of incidence of fluid flow on a square test geometry model with cross-section height H = 40 mm (D = H). The results showed that the large angle of incidence of the flow increased the value of CD, CL due to the enlargement of the flow in the downstream wake area. While the CP value also decreased due to the negative pressure gradient of the downstream area enlarged with an increase in the value of the angle of attack of the flow. The angle of attack increases the parameters CDmax = 2.33, CP = -1.87, and St = 0.09 at an angle of -30° while at an angle of 0° the value of CD = 2.05 -CPb = -1.37, St = 0.128. Changes in the angle of incidence of the flow affect the frequency of vortices. The local velocity component (u) decreased.